The Damage Induced by Blasting Excavation and Seepage Characteristics of Deep Rock under High Seepage Pressure. (18th April 2023) - Dong, Qian; Liu, Xin; Gong, Hangli; Luo, Yi; Li, Xinping; Wang, Liangjun
Abstract : By taking the blasting excavation of a deeply buried karst tunnel in the North Tianshan Mountains in China as research objects, the damage induced by blasting excavation and seepage characteristics of deep rock under high seepage pressure was investigated. The COMSOL Multiphysics® software was adopted to establish a simulation model for the blasting excavation of a deeply buried tunnel. By embedding the stress-damage-seepage multifield coupled constitutive relationship, the mechanism of the influences of factors including blasting load, geostress, and hydraulic pressure of karst caves on the blasting excavation-induced damage to, and seepage characteristic of, the surrounding rocks of the tunnel. The results indicate that blasting excavation in the karst tunnel triggers the damage of surrounding rocks, which consists of blasting-induced damage and unloading damage. The time-history curve of the variable for surrounding rock damage rises and consequently tends to a constant value. With the increases in blasting load, geostress, and hydraulic pressure of karst caves, the degree of damage to surrounding rocks is intensified; an increase in geostress will weaken the effect of blasting-induced damage to rock while increasing rock damage arising from unloading. Meanwhile, the degree of damage to the surrounding rock can affect the seepage velocity of water in the surrounding rock to a certain extent. A strong damage and seepage coupled effect occur in the blasting excavation process of the karst tunnel. The such coupled effect is strengthened little by little with the increases in the degree of surrounding rock damage and hydraulic pressures. The results are expected to provide theoretical guidance for hazard prevention and control of blasting excavation in karst tunnels under high geostress conditions.